Time course of inducibility of indirect responses in an ant‐defended plant. Issue 5 (28th March 2023) - Calixto, Eduardo Soares; Del‐Claro, Kleber; Lange, Denise; Bronstein, Judith
Abstract: Plants have evolved inducible defenses that allow them to minimize costs associated with the production of constitutive defenses when herbivores are not present. However, as a consequence, some plants might experience a period of vulnerability between damage and the onset of defense and/or between the cessation of damage and relaxation of defense. Few studies have examined the time course in the inducible protective mutualism between ants and extrafloral nectary (EFN)‐bearing plants. None has compared the inducibility of EFNs on vegetative versus reproductive parts or in response to different levels of herbivore damage. Here, we disentangle the inducibility process by evaluating extrafloral nectar production and ant attendance over time, the time course of inducibility on different plant parts, and the time course of inducibility in response to different levels of foliar damage in a Brazilian tree, Qualea multiflora (Vochysiaceae). Using simulated herbivory on leaves and flowers, we found that (a) the production of extrafloral nectar from foliar and floral EFNs, as well as ant attendance, exhibited a lag between the moment of damage and the peak of response, followed by a response peak (usually 24 h after damage) at which the defense remains at its maximum level, then declines to prestimulus levels; (b) the time course of inducibility and the peak activity did not differ between EFNs located in vegetative versus reproductive parts, except for sugar concentration, which was higher in EFNs on vegetative parts; and (c) the time course of inducibility of foliar EFNs depended on damage level. Although considered a cost‐saving strategy, inducible defenses can be disadvantageous since they can leave plants vulnerable to attack for extended periods. Our results illuminate the dynamics of the induced response and the underlying mechanisms that might mediate it, ultimately providing new insights into defense strategies employed by plants.